Protein Kinase Protocols - Reith, Alastair D. (Methods in Molecular Biology™, 2001)
As key components of many cell signaling pathways, protein kinases are implicated in a broad variety of diseases, including cancers and neurodegenerative conditions, and offer considerable potential as tractable targets for therapeutic intervention. In Protein Kinase Protocols, a panel of highly skilled laboratory investigators describe both basic and more sophisticated methods for the analysis of kinase-mediated signaling cascades, with emphasis on the identification of proteins according to their interactive relationships and the analysis of their functional properties. Described in step-by-step detail, these readily reproducible techniques offer novices quick access to a complicated field, and provide more experienced investigators many novel time-saving ploys. Emphasis is given to the critical technical steps that are often omitted from methods published in the primary literature. There are also tips on potential pitfalls and copious notes on how to adjust the protocols to work in related systems. Broad in its range of techniques and thoroughly detailed to help ensure experimental success, Protein Kinase Protocols offers both novice and experienced investigators powerful tools for understanding the functional roles of specific protein kinases within signaling cascades and for identification and evaluation of novel therapeutic targets